2020
DOI: 10.4329/wjr.v12.i9.195
|View full text |Cite
|
Sign up to set email alerts
|

Review of X-ray and computed tomography scan findings with a promising role of point of care ultrasound in COVID-19 pandemic

Abstract: As healthcare professionals continue to combat the coronavirus disease 2019 (COVID-19) infection worldwide, there is an increasing interest in the role of imaging and the relevance of various modalities. Since imaging not only helps assess the disease at the time of diagnosis but also aids evaluation of response to management, it is critical to examine the role of different modalities currently in use, such as baseline X-rays and computed tomography scans carefully. In this article, we will draw attention to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Furthermore, in critically ill COVID-19 patients, extensive coalescent and disappearing B lines affecting upper and anterior lungs, with corresponding consolidation are observed[ 33 , 63 , 64 ]. Apart from the physiological A lines, and pathological B lines, other artifacts such as C, E and Z lines, have been described[ 65 ]. Moreover, as consolidation increases, the echogenicity of the lung changes to resemble that of the liver (‘hepatic pattern’), while also demonstrating changes to the bronchi morphology.…”
Section: Imaging For Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…Furthermore, in critically ill COVID-19 patients, extensive coalescent and disappearing B lines affecting upper and anterior lungs, with corresponding consolidation are observed[ 33 , 63 , 64 ]. Apart from the physiological A lines, and pathological B lines, other artifacts such as C, E and Z lines, have been described[ 65 ]. Moreover, as consolidation increases, the echogenicity of the lung changes to resemble that of the liver (‘hepatic pattern’), while also demonstrating changes to the bronchi morphology.…”
Section: Imaging For Pulmonary Manifestations Of Covid-19mentioning
confidence: 99%
“…Although the detection of SARS-CoV-2 RNA using the RT-PCR remains the gold standard diagnostic method, the unspecific or asymptomatic initial stage of COVID-19 highlights the important role of imaging exams in assisting the early diagnosis, as well as in monitoring and identifying complications[ 32 , 29 ]. Figure 1 summarizes the main points regarding the imaging modalities used in COVID-19.…”
Section: What Do the Imaging Exams Show About The Disease?mentioning
confidence: 99%
“…Some studies have also shown high sensitivity (93%-98%) for acute respiratory distress syndrome[ 82 ]. Thus, LUS is comparable to CT, but CT shows intra-pulmonary and apical lesions more clearly and comprehensively than LUS[ 29 ]. LUS is considered advantageous for detecting smaller lesions and peripulmonary effusions as well as pleural injuries, and is a dynamic and easily accessible method[ 34 ].…”
Section: What Do the Imaging Exams Show About The Disease?mentioning
confidence: 99%
See 2 more Smart Citations